Data processing in haematology - Nelson, M. G. (1972)
The output from a Coulter model S is captured by a specially designed silent interface which visualizes the results, automatically prints the data on a continuous paper roll and transmits the information to a card punch located in a data processing room. Further requested test data and patient identification data are subsequently added manually to the punch card. The completed deck of cards is used in an off-line batch mode on a dedicated laboratory computer to format report documents, produce ward listings, and quality control information. A punch card off-line method is also described for blood group and related data.